Dating agpaitic rocks : a multi-system (U/Pb, Sm/Nd, Rb/Sr and 40Ar/39Ar) isotopic study of layered nepheline syenites from the Ilímaussaq complex, Greenland - Borst, A. M.; Waight, Tod; Finch, A. A.; Storey, Michael; Le Roux, Petrus (Lithos, 2019)
This research was funded by the Carlsberg Fund [grant nr. 2013_01_0191 to TW] and Geocenter Denmark [GreenCrimi project, grant nr. 4-2012 to AMB]. Quadlab is funded by a grant from the Villum Foundation to MS. AMB and AF thank the NERC SoS RARE project [grant nr. This research was funded by the Carlsberg Fund [grant nr. 2013_01_0191 to TW] and Geocenter Denmark [GreenCrimi project, grant nr. 4-2012 to AMB]. Quadlab is funded by a grant from the Villum Foundation to MS. AMB and AF thank the NERC SoS RARE project [grant nr. NE/M010856/1] for support during the writing of this manuscript. ] for support during the writing of this manuscript. The Ilímaussaq complex in southern Greenland is a shallow crustal composite intrusion comprising augite syenite, peralkaline granite and volumetrically dominant agpaitic nepheline syenites. Previous studies indicated a baddeleyite U-Pb age of 1160 ± 5 Ma for the augite syenite, the earliest intrusive unit of the complex. A similar crystallization age, within error, is inferred for the main sequence of agpaitic nepheline syenites. However, direct age determination of these units has been challenging because agpaitic rocks characteristically lack robust phases for in situ U-Pb dating (e.g. zircon/baddeleyite). An additional challenge is the pervasive subsolidus alteration, of which the isotopic effects are poorly constrained. Here we present new U-Pb, Sm-Nd and Rb-Sr isotopic data from whole rocks and mineral separates and a 40Ar/39Ar amphibole age of three co-genetic agpaitic nepheline syenites (kakortokite) from the lowermost exposed part of the complex. Using a multi-system geochronological approach for mineral separates and whole rocks, we explore the effects of late-stage alteration for each isotopic system. Assuming a closed-system evolution for the hydrothermal fluids (i.e. isotopically similar to the melts) and cooling within a relatively short time-frame (<0.8 Ma), we evaluate whether traditional mineral-whole rock isochron methods can provide useful age constraints ...